2015
DOI: 10.1093/geront/gnv145
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Adult Day Program Attendance on Emergency Room Registrations, Hospital Admissions, and Days in Hospital: A Propensity-Matching Study

Abstract: Findings replicate and extend results from previous research that reported a decreased reliance on costly health care services by seniors who attend adult day programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
0
9
0
1
Order By: Relevance
“…Target users included functionally impaired/frail, socially isolated or retired people and, less often, family carers. Four possible aims of day centres were stated: To provide social and preventive services (Fitzpatrick et al , 2005; Lund and Englesrud, 2008; Boen et al , 2010; Caiels et al , 2010; Dabelko-Schoeny and King, 2010; MaloneBeach and Langeland, 2011; Kuzuya et al , 2012; Iecovich and Biderman, 2013 b ; Fawcett, 2014; Marhankova, 2014; Liu et al , 2015; Shahbazi et al , 2016; Kelly, 2017). To support continued independence of attenders (Ron, 2007; Schmitt et al , 2010; Kuzuya et al , 2012; Liu et al , 2015; Kelly et al , 2016).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Target users included functionally impaired/frail, socially isolated or retired people and, less often, family carers. Four possible aims of day centres were stated: To provide social and preventive services (Fitzpatrick et al , 2005; Lund and Englesrud, 2008; Boen et al , 2010; Caiels et al , 2010; Dabelko-Schoeny and King, 2010; MaloneBeach and Langeland, 2011; Kuzuya et al , 2012; Iecovich and Biderman, 2013 b ; Fawcett, 2014; Marhankova, 2014; Liu et al , 2015; Shahbazi et al , 2016; Kelly, 2017). To support continued independence of attenders (Ron, 2007; Schmitt et al , 2010; Kuzuya et al , 2012; Liu et al , 2015; Kelly et al , 2016).…”
Section: Resultsmentioning
confidence: 99%
“…To provide social and preventive services (Fitzpatrick et al , 2005; Lund and Englesrud, 2008; Boen et al , 2010; Caiels et al , 2010; Dabelko-Schoeny and King, 2010; MaloneBeach and Langeland, 2011; Kuzuya et al , 2012; Iecovich and Biderman, 2013 b ; Fawcett, 2014; Marhankova, 2014; Liu et al , 2015; Shahbazi et al , 2016; Kelly, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent studies have found emerging evidence that ADS utilization may actually delay nursing home placement, particularly, when the caregiver is an adult child and when ADS is used in appropriate doses (Fields et al, 2014; Kelly, Puurveen, & Gill, 2016). The most promising research with regard to health care utilization has indicated that ADS use may result in lower rates of hospitalization, fewer emergency department visits, and fewer days spent in the hospital when comparing ADS users and nonusers (Kelly, 2017).…”
Section: Outcomes and Impact Of Adsmentioning
confidence: 99%
“…This causes difficulty in understanding what works, for whom and in what circumstances within the day care setting [ 19 ]. A study by Kelly [ 20 ▪▪ ] investigated the effect of day programme attendance by older people living at home on numbers and rates of emergency room admissions, hospital admissions and days in hospital. This large study matched older people attending an adult day programme with a nonattendee on the basis of similar propensity scores from clinical, psychosocial and functional co-variates.…”
Section: Outcomes Of Attending a Day Care Facilitymentioning
confidence: 99%